Obraz Polaka-imigranta przedstawiony na łamach Dialy Mail i The Sun podczas kampanii wyborczej w Wielkiej Brytanii w 2015 roku - Rożewska, Agnieszka (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Polish mass immigration to the United Kingdom after 2004 according to the British media, has had a big impact on changing the look of the contemporary Britain. Polish immigrants apear in a public debate but more often are not presented in a good light. The purpose of this paper is to examine the image of the Polish immigrants presented mainly by Daily Mail, one of the most popular newspapers in the UK, which has got a big impact on forming a negative attitude towards Eastern Europeans. The paper doesn’t describe the the scale of the Polish immigration in the UK but it tries to show the way of perception of Poles by British tabloids.